KUALITAS PELAYANAN PERIJINAN REKLAME DI BADAN PELAYANAN PERIJINAN TERPADU KOTA SEMARANG - Yusri Kurniawati; Nina Widowati; Maesaroh Maesaroh (Journal of Public Policy and Management Review, 2015)
The quality of public services that are the products of a service provided by the committee of public services to the recipient of the service. Integrated services agency permitting of Semarang is an organization operating in the fields of public service licenses. One of the licensing services organised by the licensing services semarang, BPPT Kota Semarang is the advertisement. The aim of this research is to see illustrat about the ads licensing services in BPPT Kota Semarang and also to identify the pro- and retarding the licensing services in ads board the licensing services from Semarang. There are several dimensions used to measure the quality of services provided by BPPT Kota Semarang. That is tangible, reliability, responsiveness, access and assurance. The result of this research shows that the quality of service ads licencing organized by BPPT Kota Semarang can be said is not optimal. It can be proved in dimension tangible, facilities and infrastructure available in BPPT Kota Semarang is still inadequate, in dimension reliability SOP that is in BPPT Kota Semarang not run optimal, in dimension assurance still happens licencing the delays in publishing the ads, there still illegal charges, still found pander act and discipline practice of officers who are still low. Dimensions should be improved to improve the quality of the services which is tangible, reliability and also the assurance, while the dimension that needs to be maintained and improved back is the dimensions of responsiveness and access. Efforts to improve the quality of services can be done with the use of facilities and infrastructure in a more optimized, rewards and imposing punishment on an breaktime in the form put up photo employe of the month every month to the officers who were considered most discipline, extend estimation time services , and improve coordination between the front office with the field of supervision